2019
DOI: 10.21203/rs.2.9815/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Acute respiratory tract infections among hospitalized Palestinian patients: a retrospective study

Abstract: Background: Respiratory tract infections (RTIs) are a major public health concern. This study aims to investigate the profiles and epidemiological characteristics of acute RTIs and respiratory pathogens in Palestinian hospitalized patients. Methods: Clinical samples from hospitalized patients with symptoms of acute RTIs admitted between January 2011 and December 2016 are referred to Palestinian Central Public Health Laboratory (PHCL) to identify the causative pathogen. Patients’ demographic information and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…It is noticed that from our results, the gene mutations and polymorphism in all markers are more in sample one and sample two (cases) than in sample three (control). [20] showed that gene mutations play an important role in the susceptibility of patients to pneumonia and sepsis. Also discussed the effect of genetic polymorphisms and their positive impact on calcitonin and CRP levels in patients with infection [21,22].…”
Section: Dna Sequencingmentioning
confidence: 99%
“…It is noticed that from our results, the gene mutations and polymorphism in all markers are more in sample one and sample two (cases) than in sample three (control). [20] showed that gene mutations play an important role in the susceptibility of patients to pneumonia and sepsis. Also discussed the effect of genetic polymorphisms and their positive impact on calcitonin and CRP levels in patients with infection [21,22].…”
Section: Dna Sequencingmentioning
confidence: 99%
“…Children and the elderly were the most affected with RTIs. e elderly population (≥60 years old) had the highest rates [21].…”
Section: Introductionmentioning
confidence: 99%